Effect of Increased Intravenous Hydration on Duration of Labor and Outcome of Pregnancy among Nulliparous Women: a Randomized Controlled Trial - Ashraf Direkvand Moghadam; Ali Delpisheh (Tehran University of Medical Sciences, 2013)
Background & Aim: Limitation of fluid intake in parturient can affect uterine contractions. Several studies have been conducted on the effect of hydration in labor progress and reported different results. In the present study, we evaluated the effect of over IV hydration on duration of labor and outcome of pregnancy in parturient women .   Methods & Materials: In this randomized clinical trial, 120 nulliparous women admitted to Ilam Mustafa Hospital were selected from February 2010 to December 2010. All participants had non-complicated singleton pregnancies and were randomly assigned in four groups. The first group received usual care while the second to fourth groups received lactated ringers at 60, 120 and 240 ml per hour (IV fluid groups), respectively throughout active labor phase. All women had unrestrictedly access to oral fluids. The analysis was done using the ANOVA and Chi-squared tests in the SPSS-16. The p-value less than 0.05 were considered to be statistically significant .    Results: Key variables known to affect labor outcomes were statistically similar in all groups. The mean duration of active phase of labor was lower in the intervention groups in comparison with the control group. All groups had significant differences in the duration of second stage of labor, Oxytocin augmentation, and prolonged labor. There was a trend toward a lower frequency of the Cesarean deliveries in the 240 ml group however it was not significant. There was no significant difference in the Apgar scores between groups .   Conclusion: Over IV hydration reduced duration of labor. There were no reports of poor outcomes for mother and infants .